A new species of Pherbellia (Diptera: Sciomyzidae) from Iran - Kazerani, Farzaneh; Mortelmans, Jonas; Farashiani, Mohammad Ebrahim; Thorn, Simon (Zootaxa, 2020)
Pherbellia jalili Mortelmans & Kazerani sp. nov. is described based on 5 males and 4 females. The new species is associated with old deciduous forest and is found only in the Hyrcanean forest in Iran. It is compared with its sister species, P. annulipes (Zetterstedt, 1846), and a comprehensive distribution map for both species is given. The key to species of this group of Pherbellia is updated including the Japanese Pherbellia tricolor Sueyoshi, 2001. Barcodes are generated for P. jalili sp. nov., P. annulipes, and P. nana nana (Fallén, 1820).